2021
DOI: 10.1155/2021/3284186
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Significance of Immune Cell Infiltration and Prognosis of Non-Small-Cell Lung Cancer by Bioinformatics

Abstract: Objective. To perform gene set enrichment analysis (GSEA) and analysis of immune cell infiltration on non-small-cell lung cancer (NSCLC) expression profiling microarray data based on bioinformatics, construct TICS scoring model to distinguish prognosis time, screen key genes and cancer-related pathways for NSCLC treatment, explore differential genes in NSCLC patients, predict potential therapeutic targets for NSCLC, and provide new directions for the treatment of NSCLC. Methods. Transcriptome data of 81 NSCLC … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…Additional support for the this result was the fact that in one study, a higher incidence of respiratory symptoms on initial presentation of lung cancer is associated with a poorer prognosis (23). Current studies have shown that in non-small cell lung cancer, the presence of eosinophils can prolong the survival of patients, and patients with high eosinophils levels tend to have a better prognosis (24)(25). At present, there are few studies on the mechanism of SC and more research is needed in the furture.…”
Section: Disscusionmentioning
confidence: 94%
“…Additional support for the this result was the fact that in one study, a higher incidence of respiratory symptoms on initial presentation of lung cancer is associated with a poorer prognosis (23). Current studies have shown that in non-small cell lung cancer, the presence of eosinophils can prolong the survival of patients, and patients with high eosinophils levels tend to have a better prognosis (24)(25). At present, there are few studies on the mechanism of SC and more research is needed in the furture.…”
Section: Disscusionmentioning
confidence: 94%